Indocyanine green angiography-guided thyroidectomy versus conventional thyroidectomy for preserving parathyroid function: study protocol for a randomized single-blind controlled trial - Moreno-Llorente, Pablo; García-González, Guillermo; Pascua-Solé, Mireia; García-Barrasa, Arantxa; Videla, Sebastián; Muñoz-de-Nova, José Luis, the GuiArte Study Group (Frontiers in Endocrinology, 2023)
Introduction: Angiography with indocyanine green (ICG) fluorescence performed before thyroidectomy would allow identification of the vascularization of parathyroid glands, maximizing efforts for preserving functioning glands intraoperatively. The rationale of the study was based on the hypothesis that showing the vascular pattern of the parathyroid glands by means of ICG angiography before performing the thyroidectomy could prevent permanent hypoparathyroidism. Methods and Analysis: We propose a randomized single-blind controlled and multicenter clinical trial to assess the efficacy and safety of ICG angiography-guided thyroidectomy to identify the vascular pattern of the parathyroid glands versus conventional thyroidectomy in patients scheduled for elective total thyroidectomy. Patients will be randomized 1:1 to ICG angiography-guided thyroidectomy (experimental group) or conventional thyroidectomy (control group). Patients in the experimental group will undergo ICG angiography before thyroidectomy to identify the feeding vessels of the parathyroid glands and then, post-thyroidectomy ICG angiography to predict immediate parathyroid gland function by scoring the degree of fluorescence of the glands. Patients in the control group will undergo post-thyroidectomy ICG angiography only. The primary outcome measure will be the rate of patients with permanent hypoparathyroidism. Secondary outcome measures will be rate of postoperative hypoparathyroidism, the percentage of well vascularized parathyroid glands remaining in situ, the levels of iPTH and serum calcium after surgery and the influence of the typo of vascular pattern of the parathyroid glands over these outcomes, as well as the safety profile of ICG angiography. Discussion: The results will contribute to adopt a new surgical strategy based on intraoperative ICG angiography before performing total thyroidectomy, according to which the rate of permanent hypoparathyroidism could be substantially reduced.